Structural homeostasis: compensatory adjustments of dendritic arbor geometry in response to variations of synaptic input - Tripodi, Marco; Evers, Jan-Felix (PLoS biology, 2008)
Structural homeostasis is defined as follows: developing neurons modify the growth of their dendrites to compensate for changes in synaptic density. This structural adjustment is mediated, at least in part, by postsynaptic PKA signalling.
Gesehen am 15.05.2017